Evaluation of the Implementation of Life Skills Education in Increasing the Independence and Productivity of Students - Husain Azhari; Hisyam Syafii; Rudyn Alaldaya (Pendekar: Jurnal Pendidikan Berkarakter, 2026)
Abstract: This study aims to evaluate the implementation of Life Skills Education in improving learners’ independence and productivity through a systematic literature review combined with bibliometric analysis. Data were collected from six major academic databases, resulting in 1,324 initial records. After removing 214 duplicate articles and 325 ineligible records identified through automated screening, 323 studies were retained for title and abstract screening. Of these, 285 articles were assessed for full-text eligibility, and ultimately 10 empirical studies met all inclusion criteria and were included in the final analysis. The findings reveal that Life Skills Education significantly contributes to enhancing learners’ independence in emotional, intellectual, and economic dimensions, as well as increasing productivity through employability skills, entrepreneurship, and adaptive competencies. Bibliometric mapping using VOSviewer indicates that research trends are increasingly oriented toward human development, empowerment, sustainability, and socio-economic resilience. Furthermore, the results demonstrate a paradigm shift from a traditional skill-based training model to a more holistic framework that integrates personal development, well-being, and community empowerment. This study concludes that Life Skills Education plays a strategic role in non-formal education by fostering self-reliant and productive individuals. The findings also provide empirical and theoretical contributions for policymakers and educators in developing more integrated, context-based, and sustainable educational programs.Abstrak: Studi ini bertujuan untuk mengevaluasi implementasi Pendidikan Keterampilan Hidup dalam meningkatkan kemandirian dan produktivitas peserta didik melalui tinjauan literatur sistematis yang dikombinasikan dengan analisis bibliometrik. Data dikumpulkan dari enam basis data akademik utama, menghasilkan 1.324 catatan awal. Setelah menghapus 214 artikel duplikat dan 325 catatan yang tidak memenuhi syarat yang diidentifikasi melalui penyaringan otomatis, 323 studi dipertahankan untuk penyaringan judul dan abstrak. Dari jumlah tersebut, 285 artikel dinilai kelayakannya untuk teks lengkap, dan akhirnya 10 studi empiris memenuhi semua kriteria inklusi dan dimasukkan dalam analisis akhir. Temuan menunjukkan bahwa Pendidikan Keterampilan Hidup secara signifikan berkontribusi pada peningkatan kemandirian peserta didik dalam dimensi emosional, intelektual, dan ekonomi, serta meningkatkan produktivitas melalui keterampilan kerja, kewirausahaan, dan kompetensi adaptif. Pemetaan bibliometrik menggunakan VOSviewer menunjukkan bahwa tren penelitian semakin berorientasi pada pengembangan manusia, pemberdayaan, keberlanjutan, dan ketahanan sosial-ekonomi. Lebih lanjut, hasil penelitian menunjukkan pergeseran paradigma dari model pelatihan berbasis keterampilan tradisional ke kerangka kerja yang lebih holistik yang mengintegrasikan pengembangan pribadi, kesejahteraan, dan pemberdayaan masyarakat. Studi ini menyimpulkan bahwa Pendidikan Keterampilan Hidup memainkan peran strategis dalam pendidikan non-formal dengan membina individu yang mandiri dan produktif. Temuan ini juga memberikan kontribusi empiris dan teoretis bagi para pembuat kebijakan dan pendidik dalam mengembangkan program pendidikan yang lebih terintegrasi, berbasis konteks, dan berkelanjutan.